2021
DOI: 10.1063/5.0045261
|View full text |Cite
|
Sign up to set email alerts
|

Polarization singularities: Progress, fundamental physics, and prospects

Abstract: Polarization singularities, describing the points where the state of polarization is indeterminate, reveal the polarization topology in vectorial optical fields, which include two-/three-dimensional topologies such as C-points, V-points, L-lines, Möbius strips, links, and knots. Compared with the phase singularities, it has more parameters to manipulate, which bring forth a series of novel optical phenomena and potential applications. In this Perspective, the research progress and development of polarization s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 111 publications
0
35
0
Order By: Relevance
“…The phase singularity is associated with a phase (scalar) vortex of a beam or with the helical wavefront. The polarization singularity occurs in beams with spatially varying polarization distribution [45,46].…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase singularity is associated with a phase (scalar) vortex of a beam or with the helical wavefront. The polarization singularity occurs in beams with spatially varying polarization distribution [45,46].…”
Section: Problem Formulationmentioning
confidence: 99%
“…In recent years, the study of the vector vortex beams with the phase and polarization singularities has been of particular interest [41][42][43][44][45][46]. Various types of cylindrical vector beams (CVBs) with helical wavefronts and spatially nonuniform state of polarization, such as Laguerre-Gauss (LG) beams which combine spin and orbital angular momentum (OAM), were proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The axial energy flux at the focus for the initial field with azimuthal polarization in Equation ( 24) was given in [5] as:…”
Section: Focusing Of Optical Vortex With Azimuthal Polarizationmentioning
confidence: 99%
“…The study of the tight focusing of laser radiation has historically coincided with the study of beams with a polarization singularity [5]. The first work in which a subwavelength focal spot was experimentally obtained using radially polarized light was carried out in 2003 [6].…”
Section: Introductionmentioning
confidence: 99%
“…While most existing methods use mirrors made of metals or photonic-bandgap materials [21][22][23], or by utilizing the non-resonant blazing effect [24,25] to forbid the radiation of light towards unnecessary ports, recent findings of unidirectional guided resonances (UGRs) [26,27] revealed that an eigenstate itself can radiate towards only a single side of the photonic crystal (PhC) slab without the need for a mirror on the other. From the view of topological photonics [28][29][30][31], the UGRs were connected to polarization singularities [32][33][34][35][36][37][38][39][40][41] in momentum space, represented by topological charges [42][43][44][45][46][47]: they are the merged V points (vortex center of polarization fields) from paired C points (circular-polarized states) that carry the same signed half-integer topological charges on a single side. As reported, such half-charges can originate from splitting an integer charge carried by a bound state in the continuum (BIC) [42,[48][49][50] as q = 1 → 1/2 + 1/2 [27,[51][52][53], or they can be spawned from "the void" as q = 0 → 1/2 + (−1/2) [47].…”
mentioning
confidence: 99%